2017
DOI: 10.1111/aor.12955
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Evaluation of a Biological and Mechanical Aortic Valve Prosthesis Using Patient‐Specific MRI‐Based CFD

Abstract: Modeling different treatment options before a procedure is performed is a promising approach for surgical decision making and patient care in heart valve disease. This study investigated the hemodynamic impact of different prostheses through patient-specific MRI-based CFD simulations. Ten time-resolved MRI data sets with and without velocity encoding were obtained to reconstruct the aorta and set hemodynamic boundary conditions for simulations. Aortic hemodynamics after virtual valve replacement with a biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
8
34
0
Order By: Relevance
“…This may indicate that SR, which is measurable only with VFI, can detect malfunctioning MPs even though other parameters such as PSV, pressure gradients and VC are normal. Reduced SR in patients with MPs compared with BPs has also been reported by Hellmeier et al (2018) using CFD models andby Bissel et al (2018) in an MRI study, and was explained by the lower velocities in the antegrade direction, the larger orifice of MPs compared with BPs and the non-anatomic design of MPs (Bissell et al 2018;Hellmeier et al 2018). Hope et al (2010) have previously reported that patients with bicuspid valve AS predominantly have clockwise rotations.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This may indicate that SR, which is measurable only with VFI, can detect malfunctioning MPs even though other parameters such as PSV, pressure gradients and VC are normal. Reduced SR in patients with MPs compared with BPs has also been reported by Hellmeier et al (2018) using CFD models andby Bissel et al (2018) in an MRI study, and was explained by the lower velocities in the antegrade direction, the larger orifice of MPs compared with BPs and the non-anatomic design of MPs (Bissell et al 2018;Hellmeier et al 2018). Hope et al (2010) have previously reported that patients with bicuspid valve AS predominantly have clockwise rotations.…”
Section: Discussionsupporting
confidence: 61%
“…1). This geometry is not found in normal vessel and valve anatomy, and although systolic flow in the normal aortic valve and the anatomic realistic BP is formed by one jet through the orifice, the MP creates three jets from each orifice confined by the vessel wall and the central attachment (Hellmeier et al 2018). Also, a small gap exists between the leaflets and the valve housing, which is responsible for a leakage with velocities up to 4 m/s (Zakaria et al 2017).…”
Section: Discussionmentioning
confidence: 97%
“…Florian Hellmeier et al of Charité – Universitätsmedizin Berlin, Berlin, Germany, investigated the aortic hemodynamics of a biological and mechanical aortic valve prosthesis using patient‐specific magnetic resonance imaging (MRI)‐based computational fluid dynamic (CFD) simulations. Ten time‐resolved MRI data sets with and without velocity encoding were obtained to reconstruct the aorta and set hemodynamic boundary conditions for simulations.…”
Section: Valves and Vascular Supportmentioning
confidence: 99%
“…Although aortic valve replacement surgery has a self‐evident impact on hemodynamics, there is only sparse data from 4D Flow MRI studies analyzing aortic valve replacement therapies in small and heterogeneous cohorts . Some reported improved hemodynamics after valve replacement although interpatient variability of hemodynamics was high and dependent on patients’ individual aortic geometry . While such hemodynamic improvement is likely to be largely accounted for by removing the diseased valve, the contribution of the replacement valve itself to observed flow pattern changes is hardly known.…”
Section: Introductionmentioning
confidence: 99%